2022
DOI: 10.1177/20503121211069477
|View full text |Cite
|
Sign up to set email alerts
|

Survival status and predictors of mortality among HIV-positive children initiated antiretroviral therapy in Bahir Dar town public health facilities Amhara region, Ethiopia, 2020

Abstract: Background: Although there is a presence of governmental and non-governmental organizations running to provide quality HIV care services to reduce HIV-related mortality, there is rapid disease progression and death among children in developing countries including Ethiopia. Thus, this study was aimed to assess the mortality predictors of children living with HIV at Bahir Dar town public health facilities. Method: A facility-based retrospective follow-up study was conducted among 588 children who were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
2
3
1
Order By: Relevance
“…The hazard of death among HIV-positive patients was higher on the fair and poor level of the last known(recent) adherence level compared with those who have a good level of adherence. This nding is in agreement with other similar studies (17)(18)(19)22,23,(25)(26)(27). Non-adherence to the care and medication becomes less commitment to the treatment and leads to non-retain in the care, and then the patient interrupts the treatment and may develop treatment failure and opportunistic infection (12).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The hazard of death among HIV-positive patients was higher on the fair and poor level of the last known(recent) adherence level compared with those who have a good level of adherence. This nding is in agreement with other similar studies (17)(18)(19)22,23,(25)(26)(27). Non-adherence to the care and medication becomes less commitment to the treatment and leads to non-retain in the care, and then the patient interrupts the treatment and may develop treatment failure and opportunistic infection (12).…”
Section: Discussionsupporting
confidence: 94%
“…The nding from the current study belongs to higher than other studies conducted in Indian public hospitals (23), Nekemte Ethiopia (22). But some studies reported the higher nding of incidence rates compared with the current ndings (4,15,19,20,25,26). This discrepancy in results and the variation in mortality rates between these studies may be due to differences in the clinical characteristics of study participants and differences in study periods (length of follow-up), sample sizes and study settings, as our study included multi-center involvement and we included the patients those who started ART after test and treat strategy.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The estimated pooled prevalence of virological non-suppression among PLHIV in sub-Saharan Africa is 17.25% [ 6 ]. Nevertheless, the degree of virological non-suppression varies across nations and study populations, with 34% in central Tanzania [ 7 ] and 9–17% in various parts of Ethiopia—9% in Adama [ 8 ], 11% in Jimma [ 9 ], 12.2% in Delgi [ 10 ], 12.5% in the Amhara region [ 11 ], 14.5% in Adigrat [ 12 ], and 16.6% in Sekota [ 13 ].…”
Section: Introductionmentioning
confidence: 99%